INOVASI MODEL PEMBELAJARAN I‘RĀB TERINTEGRASI QIRĀ’AH DALAM MENINGKATKAN KINERJA APLIKATIF NAHWU SISWA MTs AL-KHOIR BIN BAZ 5 - Mulalic, Ahmed; Munandar, Aris (Jurnal Manajemen Pendidikan, 2025)
This study aims to describe the effectiveness of an innovative Nahwu learning model—the integrated I‘rāb-Qirā’ah model—developed during the Field Experience Practice (PPL) activity. The specific objective is to address the significant gap between theoretical mastery of Nahwu rules and their practical application in reading authentic Arabic texts at MTs Al-Khoir Islamic School Bin Baz 5. A descriptive qualitative approach was used, utilizing a comparative analysis of Lesson Plans (RPP 1-8) and reflective reports. Data diagnosis focused on three dominant error patterns identified during the evaluation of RPP 4 and RPP 5, followed by an analysis of the procedural impact of the intervention (RPP 7-8). The implementation of the integrated model, which uses Qirā’ah texts (such as Ad-Dars ar-Rābi‘) as the primary analytical tool, significantly reduced applicative errors. This reduction was evident in the accuracy of determining the correct marfū‘/manṣūb and i‘rāb mudĸāf ilaih in contextual sentences. This innovation demonstrates a highly responsive educational management strategy, utilizing PPL activities to quickly adapt instructional methods, which has implications for improving student learning outcomes and fostering a more collaborative and responsible classroom atmosphere.